Toward a Theory of Negotiation Precedent. Issue 2 (April 2016) - Crump, Larry
Abstract : It is remarkable that precedents and their use have not been well explored within the negotiation literature. In this article, I examine the sparse knowledge of precedents and offer a preliminary framework for understanding the role of precedents in negotiation, including how negotiators establish and apply them. Precedents can either evolve randomly or be created with strategic intent. Understanding precedents generally involves examining how negotiators build, adopt, avoid, and reject them. In this review of the existing literature, I identify twelve concepts and paradigms that are particularly relevant to our understanding of negotiation precedents. I also establish a research agenda and identify three methods for further developing our knowledge of precedents: applying path dependence theory from the field of international relations to a negotiation context; conducting experimental research in a laboratory setting involving subjects engaged in negotiation exercises that contain opportunities to apply precedents; and conducting field research with a focus on case methodology grounded in negotiation linkage theory and theories of negotiation dynamics. Finally, in this article, I formulate a two‐part framework on building and applying precedents, and offer managerial guidance for the negotiation practitioner. Precedents serve as a strategic technique and provide a source of power at that point in a negotiation when decisions are made.